MULTIKULTURALISME, BAHASA INDONESIA, DAN NASIONALISME DALAM SISTEM PENDIDIKAN NASIONAL - H.A.R. Tilaar (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2014)
Multiculturalism in Indonesia is growing and thriving from nationalism. Indonesian multiculturalism acknowledges the cultural diversity of ethnic groups in Indonesia, moreover as the basis of living together in Indonesia. The diversity of cultural tribes of Indonesia is not a separator but the elements of national unity. Through youth oath, Indonesian language takes an important role in an effort to unite the diversity. Language is an important part of a culture. Not only that, the use of language shows the mindset of the community members. Thus the education of language or the use of language as the national language should be started from kindergarten to higher education. The development of good Indonesian-use is important in order to strenghten the identity of Indonesia with the result that Indonesia can compete and become developed country and free from "middle income country trap.